The reduction of environmentally abundant iron oxides by the methanogen Methanosarcina barkeri - Eliani-Russak, Efrat; Tik, Zohar; Uzi-Gavrilov, Shaked; Meijler, Michael M.; Sivan, Orit (Frontiers in Microbiology, 2023)
Microbial dissimilatory iron reduction is a fundamental respiratory process that began early in evolution and is performed in diverse habitats including aquatic anoxic sediments. In many of these sediments microbial iron reduction is not only observed in its classical upper zone, but also in the methane production zone, where low-reactive iron oxide minerals are present. Previous studies in aquatic sediments have shown the potential role of the archaeal methanogen Methanosarcinales in this reduction process, and their use of methanophenazines was suggested as an advantage in reducing iron over other iron-reducing bacteria. Here we tested the capability of the methanogenic archaeon Methanosarcina barkeri to reduce three naturally abundant iron oxides in the methanogenic zone: the low-reactive iron minerals hematite and magnetite, and the high-reactive amorphous iron oxide. We also examined the potential role of their methanophenazines in promoting the reduction. Pure cultures were grown close to natural conditions existing in the methanogenic zone (under nitrogen atmosphere, N2:CO2, 80:20), in the presence of these iron oxides and different electron shuttles. Iron reduction by M. barkeri was observed in all iron oxide types within ten days. The reduction during that time was most notable for amorphous iron, then magnetite, and finally hematite. Importantly, the reduction of iron inhibited archaeal methane production. When hematite was added inside cryogenic vials, thereby preventing direct contact with M. barkeri, no iron reduction was observed, and methanogenesis was not inhibited. This suggests a potential role of methanophenazines, which are strongly associated with the membrane, in transferring electrons from the cell to the minerals. Indeed, adding dissolved phenazines as electron shuttles to the media with iron oxides increased iron reduction and inhibited methanogenesis almost completely. When M. barkeri was incubated with hematite and the phenazines together, there was a change in the amounts (but not the type) of specific metabolites, indicating a difference in the ratio of metabolic pathways. The results show the potential role of methanogens in reducing naturally abundant iron minerals in methanogenic sediments under natural energy and substrate limitations and shed new insights into the coupling of microbial iron reduction and the important greenhouse gas methane.